(untitled) (Italian Review of Legal History, 2017)
A deontological model of legal ethics took shape over the course of the Middle Ages and early modern period, thanks to contributions from both jurisprudence and moral theology. With bans on defending unjust causes and resorting to unjust means to defend a cause, the defense lawyer became part of a legal process that sought to ascertain the truth – a key contributor to the administration of justice. However, jurists and theologians made some compromises when it came to these rules, affirming that a lawyer also had a duty to defend his client to the fullest.